Modulation of intrathecal morphine-induced immunosuppression by microinjection of naloxone into periaqueductal gray - Zhang Yu; Du Li-Na; Wu Gen-Cheng; Cao Xiao-Ding (Acta Pharmacologica Sinica, 2016)
AIM: To study the involvement of opioid receptor of periaqueductal gray (PAG) and hypothalamic-pituitary-adrenal (HPA) axis in the effect of intrathecal morphine on immune function. METHODS: Rat splenic natural killer (NK) cell activity was determined by a europium release assay; the concanavalin A-induced splenic IL-2 production, TNF-beta activity, and serum TNF-alpha level were determined by colorimetric thiazolyl blue tetrazolium bromide (MTT) and gentian violet assay, and serum corticotrophin (ACTH) level by radio-immunological method after intrathecal injection of morphine and PAG microinjection of naloxone. RESULTS: Intrathecal morphine inhibited splenic NK cell activity, IL-2 production, TNF-beta activity, and increased in serum ACTH level. Microinjection of naloxone 1 microgram into PAG partially antagonized the inhibition of NK cell activity and the elevation of serum ACTH level by morphine. CONCLUSION: The opioid receptor of PAG involved in the suppression of NK cell activity by intrathecal morphine, which was accompanied by an activation of HPA axis.